University libraries and lifelong learning of older people: analysis of an experience in a digital environment - Heredia-Sánchez, Fernando (Revista General de Información y Documentación, 2023)
This article analyzes a training experience developed in a digital environment, aimed at people over 55 and taught from a university library. Its objective was to contribute to training in media and information skills by means of a workshop on the use of the catalog, access to electronic resources and participation in social networks and communication channels. Participation was 60.49% of the total registered, with a fulfillment of expectations of 4.68 out of 5. Some limitations were the date of the activity, the gender gap and not having offered further training. As conclusion, the participation of university libraries in the training of older people has strategic value and is aligned with the Sustainable Development Goals related to inclusion, access to information, lifelong learning, the fight against inequalities and the extension of the use of technologies.